Mapping the functional anatomy and topography of the cardiac autonomic innervation for selective cardiac neuromodulation using MicroCT - Kronsteiner, Bettina; Zopf, Lydia M.; Heimel, Patrick; Oberoi, Gunpreet; Kramer, Anne M.; Slezak, Paul; Weninger, Wolfgang J.; Podesser, Bruno K.; Kiss, Attila; Moscato, Francesco (Frontiers in Cell and Developmental Biology, 2022)
Background: Vagus nerve stimulation (VNS) has gained great importance as a promising therapy for a myriad of diseases. Of particular interest is the therapy of cardiovascular diseases, such as heart failure or atrial fibrillation using selective cardiac VNS. However, there is still a lack of organ-specific anatomical knowledge about the fascicular anatomy and topography of the cardiac branch (CB), which diminishes the therapeutic possibilities for selective cardiac neuromodulation. Here, we established a topographical and anatomical map of the s u p e r i o r cardiac VN in two animal species to dissect cervical and cardiac VN morphology. Methods: Autonomic nerves including superior CBs were harvested from domestic pigs and New Zeeland rabbits followed by imaging with microcomputed tomography (μCT) and 3D rendering. The data were analyzed in terms of relevant topographical and anatomical parameters. Results: Our data showed that cardiac vagal fascicles remained separated from other VN fascicles up to 22.19 mm (IQR 14.02 to 41.30 mm) in pigs and 7.68 mm (IQR 4.06 to 12.77 mm) in rabbits from the CB point and then started merging with other fascicles. Exchanges of nerve fascicles between sympathetic trunk (ST) and VN were observed in 3 out of 11 nerves, which might cause additional unwanted effects in unselective VNS. Our 3D rendered digital model of the cardiac fascicles was generated showing that CB first remained on the medial side where it branched off the VN, as also shown in the μCT data of 11 pig nerves, and then migrated towards the ventromedial site the further it was traced cranially. Conclusion: Our data provided an anatomical map of the cardiac vagal branches including cervical VN and ST for future approaches of selective cardiac neurostimulation, indicating the best position of selective cardiac VNS just above the CB point.